Influence of Drought Stress, Biofertilizers and Zeolite on Morphological Traits and Essential Oil Constituents in Dracocephalum moldavica L. - Kh Karimzadeh Asl; M Ghorbanpour; M Marefatzadeh Khameneh; M Hatami (Institue of Medicinal Plants, ACECR, 2018)
Background: Essential oil content and composition in medicinal and aromatic plants is highly affected by both biotic and abiotic factors. Objective: To investigate the effects of drought stress, zeolite and bio-fertilizers on morphological characteristics and essential oil constituents in Dracocephalum moldavica L. Methods: This experiment was conducted in the form of split factorial based on randomized complete block design with three replications in two years (2014 and 2015). The factorial experimental treatment was three levels of soil moisture (90%, 60% and 30%FC) applied to main plot, while application of zeolite (0 and 2 g per kg of soil) and bio-fertilizers (control, nitroxin, phosphate barvar-2 and nitroxin×phosphate barvar-2) were applied to sub plots. Results: Application of zeolite had the highest effect on plant height, leaf area, dry matter and flowering top branches yield (FTBY) in 90%FC and essential oil percentage and yield in 60%FC. Similarly, combination of nitroxine+phosphate barvar-2 caused maximum value of plant height, leaf area, dry matter and FTBY in 90% FC and essential oil percentage and yield in 60%FC. The GC-MS analysis of the essential oil identified 14 compounds including ester and non ester combinations. The main compounds of ester combinations were geranyl acetate and neryl acetate and the main compounds of non ester combinations were neral, geraniol and geranial. The maximum percentage of ester and non ester combinations produced in 30%FC and 60-90%FC, respectively. Conclusion: Application of zeolite accompanied by combination of nitroxine+phosphate barvar-2 produced the highest value of examined traits in D. moldavica L.